Cholesterol oxides and quality attributes of NaCl-substituted low-fat chicken sausages prepared with different antioxidants - Kazeem D. Adeyemi; Olaife S. Olatunji; Olubunmi Atolani; Hakeem Ishola; Rafiat M. Shittu; Kehinde M. Okukpe; Victoria O. Chimezie; Muinat O. Kazeem (Heliyon)
This trial investigated how different salts and antioxidants influence cholesterol oxides, microbial profiles, physicochemical properties and organoleptic characteristics of low-fat chicken sausages (CS). CS were formulated with either 2 % NaCl, CS-1; 2 % NaCl +0.02 % butylated hydroxyanisole (BHA), CS-2; 1 % NaCl + 1 % KCl + 0.25 % onionskin extract (OSE), CS-3; 1 % NaCl + 1 % KCl + 0.5 % OSE, CS-4; 1 % NaCl + 1 % K3C6H5O7 + 0.25 % OSE, CS-5 or 1 % NaCl + 1 % K3C6H5O7 + 0.5 % OSE, CS-6, cooked, and refrigerated for 45 d. The Na content in CS-1 and CS-2 (1185 ± 21 mg/100 g) was greater than that in the other CS (640 ± 18 mg/100 g). The 19-hydroxy cholesterol, 7α-hydroxycholesterol, 25-hydroxycholesterol, 5,6β-epoxycholesterol, 7β-hydroxycholesterol and carbonyl content were greater in CS-1 than in the other sausages. The OSE-treated CS group had lower levels of 7β-hydroxycholesterol and 7α-hydroxycholesterol than did the CS-2 group. CS-1 and CS-2 were lighter than the other CS. Malondialdehyde, pH, chemical composition, textural profile, microbial counts, cook loss and sensorial quality were unaffected by additives. The partial replacement of NaCl with KCl and K3C6H5O7, along with the addition of BHA and OSE, decreased the Na and cholesterol oxide contents without affecting the organoleptic qualities of low-fat CS.